2020
DOI: 10.17582/journal.jahp/2020/8.4.206.211
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Roles of Ocimum gratissimum Extract in the Control of Colibacillosis in Broilers

Abstract: Prebiotics are non-digestible substances that provide beneficial physiological effect on the host when consumed, by selectively stimulating the favourable growth or activity of beneficial bacteria such as Lactobacilli. Ocimum gratissimum is a Nigerian leafy vegetable known for its vast bioactive compounds and therapeutic use. This research aimed at identifying the prebiotic compounds present in O. gratissimum ethanolic extract and to observe their roles in the control of colibacillosis in broilers; as a natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Pseudomonas isolates were obtained from a water sample stored in a reservoir, using one-in-ten-fold serial dilutions in sterile water, and spread-plating on cetrimide agar (Titan Biotech, India), supplemented with 1% glycerol. Culture plates were incubated at 28°C for 24 h aerobically, and resultant mixed cultures from the water sample were separated to pure cultures by streaking according to modified methods of Ikele et al 14 Pseudomonas aeruginosa isolates were presumptively identified using routine biochemical tests. Antibiogram of isolates were profiled using commercial antibiotic discs (Optun, Nigeria), and the multi-drug resistant isolate was adopted for use.…”
Section: Isolation Characterization and Molecular Identification Of M...mentioning
confidence: 99%
“…Pseudomonas isolates were obtained from a water sample stored in a reservoir, using one-in-ten-fold serial dilutions in sterile water, and spread-plating on cetrimide agar (Titan Biotech, India), supplemented with 1% glycerol. Culture plates were incubated at 28°C for 24 h aerobically, and resultant mixed cultures from the water sample were separated to pure cultures by streaking according to modified methods of Ikele et al 14 Pseudomonas aeruginosa isolates were presumptively identified using routine biochemical tests. Antibiogram of isolates were profiled using commercial antibiotic discs (Optun, Nigeria), and the multi-drug resistant isolate was adopted for use.…”
Section: Isolation Characterization and Molecular Identification Of M...mentioning
confidence: 99%
“…For the total bacterial counts in the caecum, the E. coli count was reduced, while concurrently, the lactic acid bacteria count was higher. Caecal histopathology results revealed vacuolations which were interpreted as mucosal lipidosis, where the presence of short chain fatty acids produced by prebiotic fermentation would supposedly involve repairing damaged tissues via immune modulation (Ikele et al, 2020).…”
Section: In-vivo Studymentioning
confidence: 99%
“…It has been found that the use of probiotics [ 9 ], prebiotics [ 10 ], symbiotics [ 11 ] and phytogens [ 11 , 12 ] in poultry farming can alleviate the problems of antibiotics and the high cost of poultry inputs. Prebiotics were the focus of some study because of their mechanisms of action on poultry gut flora [ 13 ] and their physiological benefits on poultry health [ 14 ].…”
Section: Introductionmentioning
confidence: 99%